Language Use and Attitude among the Sherpa Speaking Community in the Kathmandu Valley - Gautam, Bhim Lal (Gipan, 2017)
This paper aims to explore the status of language use and attitude among the Sherpa speaking community in the Kathmandu valley, the multilingual capital city of Nepal. It focuses on language contact situations in different domains viz. social, cultural, personal, and official as well as media related activities where the Sherpas make use of different languages along with the use of their own mother tongue. Based on 45 questionnaires from different informants, this paper presents interesting patterns of language use and attitudes among the Sherpa speaking community in Kathmandu.